Chronic systemic exposure to IL6 leads to deregulation of glycolysis and fat accumulation in the zebrafish liver - Singh, Manoj K.; Jayarajan, Rijith; Varshney, Swati; Upadrasta, Sindhuri; Singh, Archana; Yadav, Rajni; Scaria, Vinod; Sengupta, Shantanu; Shanmugam, Dhanasekaran; Shalimar; Sivasubbu, Sridhar; Gandotra, Sheetal; et al. (Biochimica ET Biophysica Acta-Molecular and Cell Biology of Lipids, 2021)
Inflammation is a constant in Non-Alcoholic Fatty Liver Disease (NAFLD), although their relationship is unclear. In a transgenic zebrafish system with chronic systemic overexpression of human IL6 (IL6-OE) we show that inflammation can cause intra-hepatic accumulation of triglycerides. Transcriptomics and proteomics analysis of the IL6-OE liver revealed a deregulation of glycolysis/gluconeogenesis pathway, especially a striking down regulation of the glycolytic enzyme aldolase b. Metabolomics analysis by mass spectrometry showed accumulation of hexose monophosphates and their derivatives, which can act as precursors for triglyceride synthesis. Our results suggest that IL6-driven repression of glycolysis/gluconeogenesis, specifically aldolase b, may be a novel mechanism for fatty liver. This mechanism may be relevant for NAFLD in lean individuals, an emerging class of NAFLD prevalent more in Asian Indian populations.
Keywords: Aldolase b; DHAP; Inflammation; Interleukin 6; Lean NAFLD; Non-alcoholic fatty liver

Conserved RNA binding activity of phosphatidyl inositol 5-phosphate 4-kinase (PIP4K2A) - Behari, Jatin; Borkar, Pranita; Vindu, Arya; Dandewad, Vishal; Upadrasta, Sindhuri; Shanmugam, Dhanasekaran; Seshadri, Vasudevan (Frontiers in Molecular Biosciences, 2021)
Plasmodium falciparum is a causative agent for malaria and has a complex life cycle in human and mosquito hosts. During its life cycle, the malarial parasite Plasmodium goes through different asexual and sexual stages, in humans and mosquitoes. Expression of stage-specific proteins is important for successful completion of its life cycle and requires tight gene regulation. In the case of Plasmodium, due to relative paucity of the transcription factors, it is postulated that posttranscriptional regulation plays an important role in stage-specific gene expression. Translation repression of specific set of mRNA has been reported in gametocyte stages of the parasite. A conserved element present in the 3 ` UTR of some of these transcripts was identified. Phosphatidylinositol 5-phosphate 4-kinase (PIP4K2A) was identified as the protein that associates with these RNA. We now show that the RNA binding activity of PIP4K2A is independent of its kinase activity. We also observe that PIP4K2A is imported into the parasite from the host on Plasmodium berghei and Toxoplasma gondii. The RNA binding activity of PIP4K2A seems to be conserved across species from Drosophila and C. elegans to humans, suggesting that the RNA binding activity of PIP4K may be important, and there may be host transcripts that may be regulated by PIP4K2A. These results identify a novel RNA binding role for PIP4K2A that may not only play a role in Plasmodium propagation but may also function in regulating gene expression in multicellular organisms.
Keywords: malaria; posttranscriptional gene regulation; RNA-protein interaction; translation regulation

32nd National Congress of Parasitology, Pune: bringing together India's parasitologists - Purkayastha, Devatrisha; Pandit, Kushankur; Upadrasta, Sindhuri; Khilari, Ajinkya; Shanmugam, Dhanasekaran; Karmodiya, Krishanpal (Trends in Parasitology, 2025)
The 32nd National Congress of Parasitology (NCP) was held in person, 3-5 October 2024, at the Indian Institute of Science Education and Research Pune (IISER Pune), jointly organized by IISER Pune; the Council of Scientific and Industrial Research - National Chemical Laboratory, Pune; and Savitribai Phule Pune University (formerly University of Pune) in association with the Indian Society for Parasitology. The conference brought together around 250 attendees from across the country and abroad, including a diverse group of researchers, clinicians, industry experts, and students. The event provided a collaborative environment for exchanging research ideas relevant to the field of parasitology. The congress emphasized the concept of One Health, a holistic approach to address parasitic infections affecting humans and animals to promote overall health and well-being. In this TrendsTalk, the organizers provide an overview of the conference proceedings, which brought together India's vast and diverse parasitology community.